Selection procedures in sports: Improving predictions of athletes` future performance - den Hartigh, R. J. R.; Niessen, A. S. M.; Frencken, W. G. P.; Meijer, R. R. (European Journal of Sport Science, 2018)
The selection of athletes has been a central topic in sports sciences for decades. Yet, little consideration has been given to the theoretical underpinnings and predictive validity of the procedures. In this paper, we evaluate current selection procedures in sports given what we know from the selection psychology literature. We contrast the popular clinical method (predictions based on overall impressions of experts) with the actuarial approach (predictions based on pre-defined decision rules), and we discuss why the latter approach often leads to superior performance predictions. Furthermore, we discuss the "signs" and the "samples" approaches. Taking the prevailing signs approach, athletes` technical-, tactical-, physical-, and psychological skills are often assessed separately in controlled settings. However, for predicting later sport performance, taking samples of athletes` behaviours in their sports environment may result in more valid assessments. We discuss the possible advantages and implications of making selection procedures in sports more actuarial and sample-based